Tindakan Tepat Guru Kristen Menghadapi Siswa Bermasalah dalam Perannya Menuntun dan Membimbing Siswa [The Appropriate Conduct for Christian Teachers in Dealing with Disruptive Students to Fulfill Their Role in Leading and Guiding Students] - Jossapat Hendra Prijanto; Kardila Oktavia (Diligentia: Journal of Theology and Christian Education, 2021)
Classes that are conducive to support teaching and learning activities to achieve learning objectives that have been designed in such a way. But conducive classes also need the role of students as objects of learning. Students who are disciplined can create a conducive and comfortable classroom atmosphere for learning and fluency for teachers in conveying learning. The purpose of this paper is to describe the appropriate actions of the teacher when there are students who are not disciplined when learning takes place. The right course of action as a teacher is to show loving, gentle behavior and there is no need to use violence. By doing violence will not change the behavior of students for the better but instead makes students worse. As a teacher must be creative in overcoming problems and smart in choosing learning methods. The teacher becomes a shepherd who guides God's sheep to their homes, so they do not get lost. With love, we should guide each student to be able to return to God and be able to have an attitude that is obedient, responsible, and able to respond well to every education given. So as a suggestion, it is best to avoid violent acts in disciplining students but take appropriate actions in which they radiate God's love.